Design and Construction of Electric Car Chassis for KMLI Competition Needs Using Solidwork - Rifki Dwi Putranto; Zenkey Soma Mahendra; Rahaditya Dimas Prihadianto (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
The purpose of this study is to obtain a lightweight electric car frame design, providing a sense of security and comfort with the intention of being the basis for the placement of the steering, engine, battery, vehicle body, and other components for the needs of the Indonesian Electric Car Competition. This study was conducted using the Research Development method with the help of software that is capable of making a model in the form of a 3-dimensional image, in this case the software used is Solidwork software. Based on the results of the study, it can be concluded that: (1) Chassis design using Solidwork software with the design of KMLI competition needs before implementation (2) Car frame design with a 2000 watt BLDC motor specification with a 1/2 inch Black Iron Pipe frame material. (3) Analysis of the frame height when receiving a load of 100 kg is 16.5 cm with a chain ratio of 1500 rpm